The Mediating Role Of Dynamic Capability On The Influence of Intellectual Capital On Corporate Performance : A Literature Review - Nur Ajizah; Kadarisman Hidayat; Saparilah Worokinasih; Zahro ZA (Cita konsultindo, 2025)
This study aims to explore the relationship between intellectual capital (IC), dynamic capability (DC), and corporate performance (CP) while identifying gaps in the existing literature. IC, comprising human capital, structural capital, and relational capital, serves as a strategic resource for driving competitive advantage and sustainable corporate performance. Meanwhile, DC, which encompasses sensing, seizing, and reconfiguring capabilities, acts as the primary mediator in leveraging IC to respond to environmental dynamics. This study also reviews relevant literature to construct an integrative theoretical framework based on the Resource-Based View (RBV) and Dynamic Capability View (DCV). Practically, the research provides insights for companies to enhance performance through the optimization of IC and strengthening of DC. The findings identify trends, offer directions for future research, and recommend the development of strategic frameworks applicable across various sectors.